Prevalence of Quadriceps Tendonitis in Adult Trekkers - V. Paradkar, Vidula; Patil, Vinaya (Journal of Neonatal Surgery, 2025)
Background: Trekking and climbing in tall height districts are related with significant wellbeing dangers due to cruel natural conditions. Trekker tends to use both of their legs for climbing over the mountains so there are chances of overuse injury. Prolonged and intense use of quadriceps muscle may lead to pathophysiological changes in the leg, including quadriceps tendonitis. Quadriceps tendonitis is characterized by pain & swelling over proximal pole of patella. It is caused by overuse on the quadriceps tendon. Methods: A cross-sectional study was conducted among adult trekkers in Kolhapur city. Total 97 samples are included according to inclusion criteria which consist of age between 20-30 years, all genders and has experience of more than 5 years; and individual who had previous surgery of lower limb, recent trauma to hip and knee joint and congenital deformity are excluded. The study focuses on Quadriceps tendonitis in adult trekkers, so to find quadriceps tendonitis Questionnaire to evaluate quadriceps tendinopathy is used. The pain is assed with Numerical pain rating scale and tenderness with grades of tenderness. Results: Result shows 63 positive and negative 34 in individuals out of 97 individuals which results in significant prevalence of quadriceps tendonitis among adult trekkers. Percentage of positive and negative results are 64.95% and 35.05% respectively so, the prevalence of the study is 64.95%. mean values of age, year of experience, gender and outcome measures was calculated and noted in tables. Discussion: According to the mean values of all variables in positive and negative group it suggests that the intensity frequency and year experience is more in positive group as compared to negative which indicate there are high chances of getting pathological changes in the quadriceps tendon with high frequency and intensity. Conclusion:The study concludes that high frequency of trekking (i.e. climbing over the mountains) may contribute in pathophysiological changes in quadriceps tendon and development of quadriceps tendonitis. Preventive strategies such as strength training, stretching routines, appropriate trekking techniques may help reduce the risk. Further research is needed to explore long term biomechanical impacts.